Changes in Regional Parks Use: A Look at the Costa Rican Post-COVID-19 pandemic - Barrantes Chaves, Karla (2024)
COVID-19 changed the urban reality permanently. The compulsory restrictions on mobility and social distance led population to reevaluate open spaces for leisure.  This research aims to measure changes in population’s perceived usage patterns of metropolitan urban parks in Costa Rica after the COVID-19 pandemic in 2023, focusing on mobility, accessibility and visitation frequency aiming to highlight the contribution and appreciation of these spaces by the Costa Rican population.  This study uses a quantitative methodology, involving headcounts of park users, direct surveys, and detailed infrastructure surveys in the field, for the parks of la Sabana, la Paz, and el Este, located in the Greater Metropolitan Area of Costa Rica. The results show an appreciation for these spaces and an increase in visitation frequency.  Additionally, there is evidence that people are willing to travel greater distances or spend more time accessing the parks' facilities. Despite less-than-ideal maintenance and conditions, people still value them positively. It is concluded that the COVID-19 pandemic did affect usage patterns, that people value these spaces more, and that they have a broad geographic influence, mostly exceeding 2 km in distance, with a predominant presence of people from the hosting cantons of the park.